Analysis of Students' Higher Order Thinking Skills (HOTS) in Natural Science Subjects Class V Elementary School - Rizki Nurhatmanti; Bukman Lian; Adrianus Dedy (Universitas Pendidikan Indonesia (UPI), 2021)
Higher order thinking skills include critical thinking, creative thinking, problem solving, and decision making. Therefore, the difficulty that is often felt by students in developing higher order thinking skills is the difficulty in solving problems and making decisions. This research was conducted to determine the students' higher order thinking ability in the subjects of Natural Sciences (IPA) in elementary schools. The method used in this research is descriptive with a qualitative approach, namely to describe qualitative higher-order thinking skills. Data collection techniques using analysis of observations, interviews, and documentation of the results of the evaluation of science questions. The data that has been collected is then analyzed using a qualitative descriptive method. The results showed that students' high-order thinking skills in science subjects at SD Negeri 76 Palembang were included in the low category, from the evaluation results obtained an index of the percentage of students in three categories, namely, the good category was 10% with a frequency of 2 students , the less category was 20%. with a frequency of 4 students and a very poor category of 70% with a frequency of 70% of the overall HOTS indicators. So it can be concluded that students' higher-order thinking skills are still in the low category, so it needs to be further developed by strengthening students' understanding of higher-order thinking skills at levels C4 and C5. the good category was 10% with a frequency of 2 students, the less category was 20%. with a frequency of 4 students and a very poor category of 70% with a frequency of 70% of the overall HOTS indicators. So it can be concluded that students' higher-order thinking skills are still in the low category, so it needs to be further developed by strengthening students' understanding of higher-order thinking skills at levels C4 and C5. the good category was 10% with a frequency of 2 students, the less category was 20%. with a frequency of 4 students and a very poor category of 70% with a frequency of 70% of the overall HOTS indicators. So it can be concluded that students' higher-order thinking skills are still in the low category, so it needs to be further developed by strengthening students' understanding of higher-order thinking skills at levels C4 and C5.